Factors impacting hospital avoidance program utilisation in the care of acutely unwell residential aged care facility residents - Luke Testa; Tayhla Ryder; Jeffrey Braithwaite; Rebecca J. Mitchell (BMC, 2021)
Abstract Background An existing hospital avoidance program, the Aged Care Rapid Response Team (ARRT), rapidly delivers geriatric outreach services to acutely unwell or older people with declining health at risk of hospitalisation. The aim of the current study was to explore health professionals' perspectives on the factors impacting ARRT utilisation in the care of acutely unwell residential aged care facility residents. Methods Semi-structured interviews were conducted with two Geriatricians, two ARRT Clinical Nurse Consultants, an ED-based Clinical Nurse Specialist, and an Extended Care Paramedic. Interview questions elicited views on key factors regarding care decisions and care transitions for acutely unwell residential aged care facility residents. Thematic analysis was undertaken to identify themes and sub-themes from interviews. Results Analysis of interviews identified five overarching themes affecting ARRT utilisation in the care of acutely unwell residents: (1) resident care needs; (2) family factors; (3) enabling factors; (4) barriers; and (5) adaptability and responsiveness to the COVID-19 pandemic. Conclusion Various factors impact on hospital avoidance program utilisation in the care of acutely unwell older aged care facility residents. This information provides additional context to existing quantitative evaluations of hospital avoidance programs, as well as informing the design of future hospital avoidance programs.